Inherent Difference in Saliency for Generators with Different PM Materials - Eriksson, Sandra (Journal of Renewable Energy, 2014)
The inherent differences between salient and nonsalient electrical machines are evaluated for two permanent magnet generators with different configurations. The neodymium based (NdFeB) permanent magnets (PMs) in a generator are substituted with ferrite magnets and the characteristics of the NdFeB generator and the ferrite generator are compared through FEM simulations. The NdFeB generator is a nonsalient generator, whereas the ferrite machine is a salient-pole generator, with small saliency. The two generators have almost identical properties at rated load operation. However, at overload the behaviour differs between the two generators. The salient-pole, ferrite generator has lower maximum torque than the NdFeB generator and a larger voltage drop at high current. It is concluded that, for applications where overload capability is important, saliency must be considered and the generator design adapted according to the behaviour at overload operation. Furthermore, if the maximum torque is the design criteria, additional PM mass will be required for the salient-pole machine.